Experimental characterization of firebrand ignition of some wood building materials - В.А. Тараканова; Д.П. Kасымов; О.В. Гальцева; Н.В. Чичерина (Қарағанды университетінің хабаршысы. Физика сериясы)
Paper presents investigation on behaviour of wood construction material samples (plywood, oriented strand board, chipboard) in laboratory conditions as a result of a heat flux effect from naturally occurring flaming and glowing firebrands. The data of comparing ignition delay time of pine wood and wood-based construction materials (plywood, oriented strand board, chipboard) depending on the size and quantity of firebrands, initial temperature of samples, as well as the presence of air flow in firebrands falling zone is obtained. Ignition probability and conditions of wood construction materials as a result of the thermal effect of flaming and glowing pine firebrands are also studied. The obtained data allowed one to judge that according to chosen experimental parameters, the ignition time decreased with increasing air flow, as well as with an increase in the size and number of particles. It was experimentally confirmed that particle size plays a significant role in igniting of building structure. If the characteristic particle size is less than a certain characteristic value, which can be defined as the ratio of its volume to the surface area in contact with wood, then ignition mode with an abrupt maximum of temperature near phase boundary is not appear.